Effect of traffic air pollution on spirometeric parameters in Eastern Uttar Pradesh population, India - Singh, Vinay; Kumar, Devesh; Ali, Farhat; Kumar, Gaurav (International Journal of Research in Medical Sciences, 2016)
Background: In the present era of the 21st century there are lots of discussion on environmental population and its impact on life and various clinical studies done to find out the effect of air pollution on respiratory physiology, particularly pulmonary functions. Pulmonary function tests give valuable information about lung physiology in health and disease. In the present study to assess the pulmonary function test between the population groups exposed to traffic related air pollution. Methods: A cross sectional retrospective cohort study was conducted in B R D Medical College. It was done on 73 males, out of which 35 were traffic policeman (15 smokers, 20 non- smokers) and remaining 38 belonged to non- exposed control group (15 smokers, 23 non-smokers). Pulmonary function tests (PFTs) were performed with computerized spirometer. The respiratory parameter was recorded and analyzed. To check statistical of data student t-test was performed. Results: Comparison of ratio FEV₁/FVC among two populations, revealed lower values for Traffic policeman group. This difference was significant among the non-smoker (P=0.0061), while not significant among the smoker (P=0.3419). Conclusions: The respiratory parameters were changed due to traffic related air pollution. So traffic related air pollution can be a risk factor in the development of respiratory obstruction.